Changing corporate governance norms: Evidence from dual class shares in the UK - Braggion, Fabio; Giannetti, Mariassunta (Journal of Financial Intermediation, 2019)
In the UK, between 1955 and 1970, dual class shares quickly lost popularity without any regulatory intervention. The decline in the use of dual class shares was positively correlated with the relative valuations of one-share-one-vote and dual class firms, which in turn was related to media pessimism on the use of dual class shares. Following periods with high relative valuations of one-share-one-vote, one-share-one-vote firms exhibited lower returns than dual class firms suggesting that the latter were undervalued. These and other results suggest that investor demand may lead firms to abandon dual class shares.